The coding manual for qualitative researchers - Saldaña, Johnny (SAGE Publishing Inc., 2021)
"This classic manual provides the comprehensive guide to coding qualitative data. It introduces a broad array of approaches to qualitative coding, presenting the advantages and disadvantages of each to empower you to make an informed decision when choosing the appropriate option for your research project. Drawing on multiple detailed, real-world examples, the book: · Shows the step-by-step processes involved in different coding approaches · Demonstrates clearly how to apply each method of coding in a systematic way · Highlights the core skills involved in making sense of and identifying patterns in your data. This invaluable manual from world-renowned expert Johnny Saldaña illuminates the process of qualitative coding and provides clear, insightful guidance for qualitative researchers at all levels. Johnny Saldaña is Professor Emeritus of Theatre from the Herberger Institute for Design and the Arts' School of Film, Dance, and Theatre at Arizona State University"--